An Experimental Approach Regarding the Sewage Self-Cleansing Conditions. (January 2016) - Iliescu, Marius; Sandu, Mihnea; Nastase, Ilinca; Iatan, Elena; Bode, Florin
Abstract: The paper focus on the self-cleansing conditions which have to be satisfied in order to ensure the good exploitation of a sewage system. The data used in the literature refers mainly to open channel with coehsionless (sand) deposits on the bottom. The study is very useful because of the lack of data regarding the domestic sewage. An experimental setup has been conceived in order to measure velocity profiles and shear stress velocities which occur in free surface flow in a circular sewage pipe, with deposit material at the bottom. The experiments have been conducted using a PIV measurement system and the results have been compared with others works. An experimental procedure on how to measure the parameters needed to characterize the self-cleansing conditions for a sewage pipe has been defined. The paper defines also the premises for the further studies to be conducted in order to achieve final results regarding new self-cleansing conditions in a sewage pipe.